(3GSJNOGe GdCSGdjH GdcejI aj GJNGP GdbQGQGJ GdGOGQjI (B/s - (3GdYHO, LdGd GHQGgjes ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2004)
(3fXQjI GdbQGQ,GdHQeLI GdNWjI(B:(3Jchjf hUjGZI GdeTcdGJ,CSGdjH Md eTcdGJ GdHQeLI GdNWjI,eTcdI GdKfGFjI hJMdjd GdMSGSjI,fehPL Gdfbd,JNWjW heJGHYI GdeTQhYGJ,fXQjI GdeHGQjGJ,GdHQeLI GdNWjI HGdCYOGO GdUMjMI,HQeLI GdCgOGa,GdHQeLI GdNWjI GdOGdjI,GdHQeLI GdEMJeGdjI,fXQjI Uaha GdEfJXGQ,feGPL GdeMGcGIs
(3GdeQGLY U(B.493s
Keywords: (3GdGSGdjH GdcejIs; (3GdHQeLI GdNWjIs; (3GdbQGQGJ GdGOGQjIs